Determinants of Job Satisfaction among University Teachers at the Central Department of Education - Koirala, Padma; Khatiwada, Shambhu P. (Molung Educational Frontier, 2026)
This paper assesses the influencing factors of job satisfaction among university teachers at the Central Department of Education at Tribhuvan University, Nepal. Job satisfaction refers to the level of pleasure or contentment an individual experiences in their job. Professional stress is a psychological state influenced by the nature of the job, the work environment, compensation, and relationships with colleagues and supervisors. The level of job satisfaction is influenced by various factors, such as employee well-being, motivation, commitment, and performance. This paper uses a cross-sectional research design and a questionnaire based on Paul Spector's Job Satisfaction Survey model. This model focuses on various aspects such as pay, promotion, supervision, fringe benefits, and working conditions, among others, to assess employee satisfaction. Data analysis involved descriptive statistics and Pearson correlation analysis to examine the relationship between job satisfaction and variables such as age and job tenure. This paper revealed an ambivalent level of overall job satisfaction among teachers, with no significant relationship found between overall job satisfaction and age and job tenure, although a few significant correlations were obtained with some of the dimensions of job satisfaction. The findings highlight the complexity of job satisfaction and the importance of considering various factors within the unique cultural and educational context of Tribhuvan University. By examining the state of job satisfaction within the academic community of the Central Department of Education, the research provides a foundation for future initiatives aimed at encouraging a more positive and supportive work environment.